Virtual merge and split at intersection for vehicle platooning based on self-triggered pinning consensus control. (1st February 2023) - Tanaka, Ayaka; Kobayashi, Koichi; Yamashita, Yuh
ABSTRACT: In this paper, a new method of vehicle platooning at an intersection is proposed based on self-triggered pinning consensus control. Using the proposed method, collision avoidance is achieved with no vehicles stopping/backing. First, the outline of self-triggered pinning consensus control is explained. Next, the problem setting of vehicle platooning is given, and virtual merge and split of vehicle groups are proposed. Furthermore, performance analysis of self-triggered pinning consensus control for vehicle platooning at an intersection is conducted. Finally, a numerical simulation is presented to demonstrate the proposed method. GRAPHICAL ABSTRACT: UF0001